Review of psychiatric services to mentally disordered offenders around the Pacific Rim. (19th November 2013) - Every‐Palmer, Susanna; Brink, Johann; Chern, Tor P.; Choi, Wing‐Kit; Hern‐Yee, Jerome Goh; Green, Bob; Heffernan, Ed; Johnson, Sarah B.; Kachaeva, Margarita; Shiina, Akihiro; Walker, David; Wu, Kevin; et al.
Abstract This article was commissioned to collate and review forensic psychiatric services provided in a number of key Pacific Rim locations in the hope that it will assist in future dialogue about service development. The Board of the Pacific Rim College of Psychiatrists identified experts in forensic psychiatry from Australia, Canada, China, Hong Kong, Japan, Russia, Singapore, Taiwan, and the US. Each contributor provided an account of issues in their jurisdiction, including mental health services to mentally disordered offenders in prison, competence or fitness to stand trial, legal insanity as a defense at trial, diminished responsibility, and special forensic services available, including forensic hospitals and community forensic mental health services. Responses have been collated and are presented topic by topic and country by country within the body of this review. The availability of mental health screening and psychiatric in‐reach or forensic liaison services within prisons differed considerably between countries, as did provisioning of community forensic mental health and rehabilitation services. Diversion of mentally disordered offenders to forensic, state, or hybrid hospitals was common. Legal constructs of criminal responsibility (insanity defense) and fitness to stand trial ("disability") are almost universally recognized, although variably used. Disparities between unmet needs and resourcing available were common themes. The legislative differences between contributing countries with respect to the mental health law and criminal law relating to mentally disordered offenders are relatively subtle. The major differences lie in operationalizing and resourcing forensic services.